Optimalisasi Potensi dan Konservasi Kelautan dalam Mendukung Sustainable Blue Economy di Kawasan Pantai Sendang Biru - Azis, Abdul; Wahyuningsih, Rani Destia; Priambodo, Magistyo Purboyo; Annisya, Annisya (Program Studi Teknik Kelautan Universitas Abdurachman Saleh Situbondo, 2025)
Abstract This study examines the optimization of marine potential and conservation to support a sustainable blue economy in the coastal area of Sendang Biru, Malang Regency. The primary focus is on empowering fishermen through sustainable economic approaches such as digitalization of fisheries marketing, business-to-business (B2B) and business-to-customer (B2C) models, and the implementation of circular economy in marine waste management. The research method includes literature review and policy analysis based on secondary data. The results indicate that integrating technology and community empowerment significantly contributes to improving fishermen's welfare and enhancing the efficiency of the fisheries supply chain. The study concludes that collaboration among fishermen, the government, and the private sector is essential in building a sustainable marine economic ecosystem. Keywords: marine conservation, sustainable blue economy, fisheries digitalization, circular economy, Sendang Biru.